The strategy and tools of the Republic of Korea's soft power - O. A. Duguzheva (Современная наука и инновации, 2025)
With the help of soft power policy, the state can achieve its goals by spreading its values, culture, using resources that make the country attractive to citizens of other countries. Soft power is based on such resources as cultural and value attractiveness, attractiveness of the economic model of the country's development, attractiveness of the political model. The article is devoted to the study of the Korean wave Hallyu, the history of its origin, features of the formation of the soft power of the Republic of Korea, popularization in the international environment. The author applied the methods of institutional and structural-functional analysis. The tools and directions of the soft power of the Republic of Korea are considered. The history and promotion of the Korean waves Hallyu, Hallyu 2.0, Hallyu 3.0, Hallyu 4.0 were considered. Significant resources of the soft power of the Republic of Korea are Korean cinema (dramas and films), the music industry (mainly Korean pop music or K-pop), with the help of which information about the country is disseminated, its values are broadcast, the number of tourists increases, etc. Conclusion. The strategy, resources, and soft power instruments of the Republic of Korea are analyzed. The emergence and successful spread of the phenomenon of the Korean wave Hallyu is explained.